1976
DOI: 10.1073/pnas.73.12.4653
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics in clinical medicine: prevention by forms of coenzyme Q of the inhibition by adriamycin of coenzyme Q10-enzymes in mitochondria of the myocardium.

Abstract: Adriamycin inhibits the succinoxidase system and the NADH-oxidase system. Both of the intact mitochondrial enzymes and the pentane-extracted preparations are inhibited. The inhibition can be prevented by a molar ratio of coenzyme to adriamycin of 3:1 for coenzyme QIo (ubiquinone) Adriamycin and related anthracyclines are now widely used in clinical medicine for the chemotherapy of cancer (1). Carter and Blum (2) summarized the wide range of clinical antitumor activities and the integration of adriamycin into c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…(12). Subsequently, coenzyme Qlo has been used to prevent the inhibition by Adriamycin of coenzyme Qlo enzymes and to partially prevent the cardiotoxic side effect of the drug in animal studies (7,14 (9), using rat liver microsomes and Adriamycin. Free-radical production by Adriamycin in animal cells and ensuing lipid peroxidation have been suggested as possible contributing factors for cardiac damage by Adriamycin (25).…”
Section: Resultsmentioning
confidence: 99%
“…(12). Subsequently, coenzyme Qlo has been used to prevent the inhibition by Adriamycin of coenzyme Qlo enzymes and to partially prevent the cardiotoxic side effect of the drug in animal studies (7,14 (9), using rat liver microsomes and Adriamycin. Free-radical production by Adriamycin in animal cells and ensuing lipid peroxidation have been suggested as possible contributing factors for cardiac damage by Adriamycin (25).…”
Section: Resultsmentioning
confidence: 99%
“…Decreased mitochondrial respiratory control reflecting a decrease in the maximum oxidative capacity was reported by Ferrero and coworkers (46). Folkers et al showed that doxorubicin inhibits the succinate dehydrogenasecoenzyme Q reductase and the NADH oxidase-coenzyme Q reductase systems of beef heart mitochondria (85,86). More recently, Goormaghtigh and his coworkers, and others have shown that doxorubicin inhibits cytochrome c oxidase by binding with and removing the mitochondrial membrane cardiolipin necessary for mitochondrial enzyme function (59,60,124).…”
Section: Disturbances In Energyproductionmentioning
confidence: 90%
“…Such a decrease was observed both in experimental animals (2) and humans (3). It was suggested that a defi ciency of Q10 in the pancreas could impair bioenergetics, the generation of ATP, and the biosynthesis of insulin (4). In diabetes, CoQ 10 defi ciency may be linked to impaired beta-cell function and the development of insulin resistance (5).…”
Section: Ginter Ementioning
confidence: 99%